Macqueripe [sic] Bay, Trinidad, B.W.I. - (:unkn) unknown (Photos,Cum privilegio, James Books Store, 2011)
A view of Maqueripe Bay located on the northern coastline of Chaguaramas, Trinidad.
Colour: Sepia with hues of green; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Inlets--Trinidad and Tobago; Beaches--Trinidad and Tobago; Bays--Trinidad and Tobago; Bathing beaches--Trinidad and Tobago; Maqueripe Bay